Quasi-2D modeling of hydro-sedimentological processes in large lowland river-floodplain systems - Basile, Pedro A. (2007)
In this work a quasi two-dimensional model called CTSS8_FLUSED, suitable for the time-dependent water and fine sediment transport processes simulation in large lowland river systems, including their floodplains, is presented. Water flow and sediment equations are represented by means of the interconnected cells scheme. Different simplifications of the Saint Venant momentum equation are used to represent the discharge laws between fluvial cells. Spatially-distributed transport, deposition and erosion processes of fine sediments throughout the river-floodplain system can be simulated. The model is particularly appropriated for simulations at large space scale and for both short and long-term scale. The hydrodynamic module of the model is applied along a 205 km reach of the Paraná River, Argentina, and involving a river-floodplain area of nearly 8000 km2. Hydraulic processes in the main stream-floodplain system were simulated. The numerical simulations were carried out for both low and mean river water stages and satisfactory results were obtained during model calibration and validation.